Coherence of Regional Independence and Welfare of Regional Communities in the Perspective of the Welfare State - Cynthia Hadita; Susi Dwi Harijanti; Afnila; Keizerina Devi Azwar (Indonesian Journal of Business Analytics, 2023)
Crucially, regional independence is an important part of creating welfare for regional communities which will be studied from the perspective of the welfare state. The research method used is normative juridical with a doctrinal approach. The results showed that there is a coherence between regional independence and the welfare of the people in the region that independent regional government will be able to optimize the regional potential for regional needs.